2012
DOI: 10.1088/0004-637x/757/1/48
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Dwarf Galaxies in Clusters and the Origin of Intracluster Stars. Ii. Cosmological Simulations

Abstract: We combine a N-body simulation algorithm with a subgrid treatment of galaxy formation, mergers, and tidal destruction, and an observed conditional luminosity function Φ(L|M ), to study the origin and evolution of galactic and extragalactic light inside a cosmological volume of size (100 Mpc) 3 , in a concordance ΛCDM model. This algorithm simulates the growth of large-scale structures and the formation of clusters, the evolution of the galaxy population in clusters, the destruction of galaxies by mergers and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 57 publications
6
52
0
Order By: Relevance
“…On the other hand, Murante et al (2007) suggested that the merging events prior to the formation of the cluster are the main contributor to the ICL. Through a set of cosmological simulations, Martel et al (2012) concluded that destruction of galaxies by mergers dominates over the tidal stripping by about an order of magnitude at all redshifts. In these simulations, the bulk of the ICL was made by intermediate size satellites with halo mass in the range of 10 11 − 10 12 M .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Murante et al (2007) suggested that the merging events prior to the formation of the cluster are the main contributor to the ICL. Through a set of cosmological simulations, Martel et al (2012) concluded that destruction of galaxies by mergers dominates over the tidal stripping by about an order of magnitude at all redshifts. In these simulations, the bulk of the ICL was made by intermediate size satellites with halo mass in the range of 10 11 − 10 12 M .…”
Section: Resultsmentioning
confidence: 99%
“…The projected surface density of intracluster stars near critical curves, typically ∼ 50 kpc from the cluster center, usually contributes a lensing convergence κ 10 −3 -10 −2 (Zwicky 1951;Lin & Mohr 2004;Zibetti et al 2005). These stars may have been tidally stripped from cluster galaxies throughout the assembly history of the brightest central galaxy (BCG), or have formed in situ within tidally ejected intracluster clouds (Martel et al 2012;Contini et al 2014;Cooper et al 2015). Despite these low values of κ , a similar line of reasoning as that in Eqs.…”
Section: Microlensing By Intracluster Starsmentioning
confidence: 99%
“…van Dokkum et al 1999), and that the intra-cluster light builds up over time, probably by disruptions of relatively low mass galaxies (Martel et al 2012). Also we know that BCGs have to grow in stellar mass over time (e.g.…”
Section: A Simple Quenching Modelmentioning
confidence: 99%